Thermal activation delayed fluorescence type ionic material and application of perovskite quantum dots thereof in passivation
By doping the surface of perovskite quantum dots with thermally activated delayed fluorescence ionic liquid materials, the problem of surface defect passivation of perovskite quantum dots was solved, improving their stability and photoelectric performance, and achieving high-efficiency OLED device performance.
Patent Information
- Application Number
- CN202411983030.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-12-16
AI Technical Summary
Existing technologies are insufficient to effectively passivate surface defects in halide perovskite quantum dots, leading to decreased optical performance and inadequate stability, which in turn affects the performance of optoelectronic devices.
OLED devices are fabricated by using thermally activated delayed fluorescence ionic liquid materials as ligands and combining them with the surface of perovskite quantum dots through doping. The TADF properties and good solubility of these materials are used to passivate surface defects.
This improves the stability and photoelectric properties of perovskite quantum dots, enhances the environmental stability and photoelectric properties of OLED devices, and meets the requirements for high color purity displays.
Smart Images

Figure CN121135700A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of luminescent materials, specifically to the molecular design of ionic TADF materials and their application in passivating perovskite defects. Background Technology
[0002] Metal halide perovskite quantum dots (PQDs) have attracted much attention due to their narrow and symmetrical photoluminescence (PL) peaks, high photoluminescence quantum yield (PLQY), tunable band gaps, and solution processing properties, and are considered one of the most promising optoelectronic materials. Because PQDs have a large specific surface area, surface chemical engineering is needed to reduce nonradiative recombination caused by surface defects, improve PQD stability, and enable their use in high-performance optoelectronic devices such as light-emitting diodes, solar cells, and photodetectors. However, the optical properties of halide perovskite quantum dots are often affected by defects formed by surface halide vacancies and ligand detachment. Due to their ionic nature, the ligands bound to the surface of halide perovskite quantum dots are highly dynamic. Therefore, the necessary purification process leads to ligand separation and removal of surface halides. Despite defect tolerance, the separation of ligands and halide atoms from the surface due to the formation of nonradiative surface traps significantly reduces PLQY. Surface ligands not only affect the PLQY of PQDs, but also their shape and size, as well as their colloidal stability and assembly into thin films, which are crucial for device applications. Therefore, the passivation of ligands and surface traps plays a vital role in modulating stability, luminescence, or carrier transport, and may even induce novel functions. Interestingly, surface traps can be removed through post-synthetic chemical treatment.
[0003] In-situ ligand substitution and post-synthetic ligand exchange are two common methods for replacing long-chain insulating ligands. However, balancing colloidal stability and short ligand passivation while maintaining the confinement of perovskite quantum dots is a challenge. In the synthetic reaction, the aliphatic chain length of the ligand and the binding energy of the functional groups significantly influence the shape and size of the quantum dots. Furthermore, short-chain ligands have low boiling points, making them unsuitable for high-temperature hot-injection reactions. Post-synthetic ligand exchange requires the removal of the original long-chain ligands using polar solvents. However, the high ionic structure and low phase stability of perovskite quantum dots limit the choice of usable ligand solvents. Strongly polar solvents, such as methanol, can disrupt the structural stability of perovskite nanocrystals. Ligand loss during post-processing leads to the aggregation or even decomposition of perovskite quantum dots. Therefore, an effective ligand exchange strategy is crucial for improving the stability and charge transfer performance of perovskite quantum dots, especially for small-sized perovskite quantum dots.
[0004] Functional groups in ligand chemistry play a crucial role in the binding of perovskite quantum dots to their surfaces, with acid-base theory being the dominant mechanism. In this regard, numerous studies have focused on alkylphosphonic acids as surface ligands due to their strong interaction capabilities with perovskite quantum dots. Through post-synthetic surface treatment, the parent OAm / OA ligands can also be substituted with alkylphosphonic acid ligands, which preferentially interact with negatively charged PO4 groups. - Terminal binding allows P=O and P-OH groups to freely form hydrogen bonds between ligands. Phosphonate ligands can also strongly passivate the PQDs surface, resulting in a well-purified colloidal CsPbBr3 PQDs solution. Ligands with sulfofunctional groups, such as sulfonic acids, sulfates, or thioethers, are also effective because they bind to Pb. 2+ Strong ion interactions have also been explored for enhancing stability and photoluminescence. Bidentate ligands, possessing two functional groups that can bind to PQDs, have attracted particular attention due to their ability to improve PQD stability through chelation. Bidentate ligands show great promise for efficient surface passivation and photoluminescence enhancement. Importantly, the biterminated PQDs retain their photoluminescence efficiency even after several washes. Zwitterionic ligands containing quaternary ammonium salts and acid groups have also been shown to improve the durability and stability of PQDs because they are able to anchor tightly to the PQD surface.
[0005] This invention utilizes TADF as its core to prepare thermally activated delayed-fluorescence ionic ligands that can bind to surface defects in perovskite quantum dots. This not only improves the stability and photoelectric properties of perovskite quantum dots but also endows them with TADF characteristics. Building upon previous work, this invention relates to a method for preparing a thermally activated delayed-fluorescence ionic liquid material and its device. The material comprises an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer, an electron injection layer, and a cathode. The light-emitting layer is prepared from perovskite quantum dots passivated by the thermally activated delayed-fluorescence ionic liquid material. The device is fabricated using a spin-coating wet method. This ionic liquid material includes three components: TADF groups, modifying groups, and linking groups, thereby enabling the electroluminescence spectrum of the OLED device to meet the requirements of high color purity displays. Summary of the Invention
[0006] The purpose of this invention is to propose a method for synthesizing a thermally activated delayed fluorescence (TADF) ionic liquid material and its applications. This material possesses TADF properties, enabling perovskite quantum dots synthesized using this material to exhibit TADF characteristics. It is a novel ionic ligand material with a simple synthesis process and can be used to passivate defects on the surface of perovskite quantum dots. Perovskite quantum dots synthesized using this material, and organic light-emitting diodes (OLEDs) fabricated using these perovskite quantum dots, achieve excellent photoelectric performance. This invention designs a thermally activated delayed fluorescence (TADF) ionic liquid material and its synthesis process.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] 1. This invention provides a method for synthesizing thermally activated delayed fluorescence ionic liquids and their applications, and discloses an organic electroluminescent device thereof, wherein the light-emitting layer is doped with a thermally activated delayed fluorescence ionic liquid as a ligand material into the main ligand material oleic acid / oleylamine to participate in the synthesis of perovskite quantum dots; further, the doping concentration of the thermally activated delayed fluorescence ionic liquid is 30 wt%; doping concentration refers to the mass percentage of the guest material to the host material.
[0009] 2: Another objective of this invention is to provide a method for synthesizing the above-mentioned thermally activated delayed fluorescence ionic liquid material. The process is simple, the purification is easy, and the yield is high. This method enables the perovskite quantum dots synthesized using the material to not only have TADF properties, but also to significantly improve the photoelectric properties and environmental stability of the perovskite quantum dots.
[0010] 3: Another objective of this invention is to provide an OLED device using a perovskite synthesized with the above-mentioned thermally activated delayed fluorescence ionic liquid, which enables the electroluminescence spectrum of the OLED device to meet the requirements of high color purity displays while improving the environmental stability of the device.
[0011] 4: To achieve the above objectives, the present invention provides a thermally activated delayed fluorescence ionic liquid with the structure shown in formula (1);
[0012] Equation (1),
[0013]
[0014] This material has advantages such as low synthesis cost, simple synthesis, environmental friendliness, good passivation effect on surface defects of perovskite quantum dots, and high device efficiency, providing an important reference for further optimizing the application of perovskite quantum dots in optoelectronic devices.
[0015] 5: A method for synthesizing a thermally activated delayed fluorescence ionic liquid according to the present invention includes the following steps:
[0016] Step 1: 6-(4-(((6-bromohexyl)oxy)methyl)phenoxy)-N,N-dimethylhexane-1-amine and 4-hydroxycarbazole are attached to the 4-position of carbazole by a substitution reaction to obtain intermediate 1, the structure of which is shown in formula (2).
[0017] Equation (2),
[0018]
[0019] Step 2: 2,8-difluoro-dibenzothiophene, 5,5-dioxide and intermediate 1 are given by electrophilic substitution reaction to obtain intermediate 2, the structure of which is shown in formula (3);
[0020] Equation (3),
[0021]
[0022] Step 3: Intermediate 2 and 1-bromoethane are subjected to a Menschutkin reaction to obtain a thermally activated delayed fluorescence ionic liquid. The thermally activated delayed fluorescence ionic liquid DPCN-Br has the structural formula shown in formula (1). In the application of the thermally activated delayed fluorescence ionic liquid material of the present invention, the thermally activated delayed fluorescence ionic liquid material is used as a doping ligand to participate in the synthesis of perovskite quantum dots together with oleic acid / oleylamine. When used in the light-emitting layer of an electroluminescent diode, the organic electroluminescent device structure is anode / hole injection layer / hole transport layer / light-emitting layer / electron transport layer / electron injection layer / cathode, wherein the perovskite quantum dots synthesized using this material are used as the light-emitting layer.
[0023] The beneficial effects of this invention are as follows: The thermally activated delayed fluorescence ionic liquid material of this invention combines the long lifetime emission characteristics of TADF and the good solubility of alkyl chains, as well as the characteristic that tertiary amines can react with haloalkanes to form ammonium salts and passivate surface defects of perovskite quantum dots; its synthesis method is simple, easy to purify, and has a high yield; the perovskite quantum dots synthesized using the above-mentioned thermally activated delayed fluorescence ionic liquid material have good stability as the OLED light-emitting layer, thereby greatly improving the photoelectric performance and environmental stability of OLED devices. Attached Figure Description
[0024] Figure 1 This is a structural diagram of the device used in this invention.
[0025] Figure 2 The UV-Vis absorption and photoluminescence spectra of PQDs and DPCN-Br-PQDs are shown.
[0026] Figure 3 Fourier transform infrared spectra of PQDs and DPCN-Br-PQDs.
[0027] Figure 4 The JVL performance curves for PQDs and DPCN-Br-PQDs devices are shown. Detailed Implementation
[0028] The following examples and... Figure 1-4 Further explanation of the present invention:
[0029] The technical solution of the present invention will be clearly and completely described below. All instances obtained by those skilled in the art based on the embodiments of the present invention without inventive effort are within the scope of protection of the present invention.
[0030] [Reaction Route Map]
[0031]
[0032] (1) Synthesis of monomer 1: Under a nitrogen atmosphere, 4-hydroxycarbazole (4.5 g, 24.63 mmol) and 6-(4-(((6-bromohexyl)oxy)methyl)phenoxy)-N,N-dimethylhexane-1-amine (6.8 g, 16.42 mmol) were added to an acetone (100 mL) solution containing potassium carbonate (6.8 g, 49.28 mmol) at room temperature. The mixture was heated to 65 °C and stirred vigorously for 24 h. After cooling the mixture to room temperature, the insoluble solids were removed by filtration. The mixture was washed repeatedly with dichloromethane 2-3 times. The resulting solution was concentrated under vacuum to obtain the crude product. The crude product was purified by silica gel column chromatography to obtain a pale yellow liquid, namely monomer 1 (7.1 g, yield 84%).
[0033] (2) Synthesis of monomer 2: In a nitrogen atmosphere, monomer 1 (7.07 g, 13.69 mmol) and 2,8-difluoro-dibenzothiophene, 5,5-dioxide (1.5 g, 6.0 mmol) were added to tetrahydrofuran (60 mL) containing sodium hydride (2.8 g, 119.05 mmol) at room temperature. After stirring at room temperature for 24 h, the sodium hydride was quenched with water. The crude product was obtained by filtration and washed repeatedly with dichloromethane 2-3 times. The resulting solution was concentrated under vacuum and purified by silica gel column chromatography to obtain a light green liquid, namely monomer 2 (6.1 g, yield 82%).
[0034] (3) The obtained monomer 2 was dissolved in N,N-dimethyl sulfoxide and mixed with tetrahydrofuran and excess 1-bromoethane. The mixture was stirred vigorously at 75°C for 72 h under a nitrogen atmosphere, then concentrated under vacuum and purified by silica gel column chromatography to obtain the target product DPCN-Br.
[0035] Example 1: When the doping concentration of DPCN-Br was 30 wt%, CsCO3, OA, and ODE (20 mL) were added to a 50 mL three-necked flask. The mixture was dried under vacuum at 120 °C for 60 min, then nitrogen was introduced, and the solution was heated to 150 °C and held for 15 min to allow the CsCO3 and OA to react completely. Finally, the solution temperature was lowered to 120 °C for further use. The designed ion ligand concentrations, along with OA, OAm, PbBr2, and ODE (20 mL), were placed in a 50 mL three-necked flask and dried under vacuum at 120 °C for 60 min. Then, under a nitrogen atmosphere, the OAm solution was injected into the mixture, and the reaction was allowed to proceed for 15 min, forming a clear and transparent solution. The temperature was then raised to 175 °C, and 2 mL of cesium oleate solution was rapidly injected into the flask. After reacting for 5-10 s, the reaction mixture was rapidly cooled in an ice-water bath to obtain a bright green CsPbBr3 quantum dot stock solution. The stock solution was divided into four centrifuge tubes and mixed with ethyl acetate at a volume ratio of 1:2. The mixture was centrifuged at 12000 rpm for 6 min, and the precipitate was dispersed in 3 ml of n-hexane. This purification process was repeated 2-3 times, and the final dispersion in n-hexane was used for later use. Fabrication and performance evaluation of organic electroluminescent devices using perovskite quantum dots as the emitting layer, synthesized with 10 wt% doped ionic ligands:
[0036] The fabrication steps for an organic electroluminescent device using perovskite quantum dots synthesized with DPCN-Br ligand doping as the emitting layer are as follows:
[0037] (1) Pretreatment of glass substrate: Select transparent electrode glass substrate (3.2×3.2mm) with indium tin oxide (ITO) film. Sonicate the glass substrate with indium tin oxide film with ITO cleaning solution, deionized water, acetone, isopropanol and ethanol for 30 minutes respectively. Then, put these substrates into an ultraviolet ozone cleaner for 15 minutes to obtain pretreated glass substrate.
[0038] (2) Spin coating: The pretreated glass substrate is spin-coated at low speed (500 rpm, 10 s) and high speed (3000 rpm, 120 s) using a spin coater to uniformly cover the entire glass substrate with PEDOT:PSS, and then annealed for 20 min. After cooling to room temperature, PVK is spin-coated on the PEDOT:PSS surface at high speed (3000 rpm, 120 s) for 60 s, and then annealed for 10 min. After cooling to room temperature, a light-emitting layer is spin-coated, which is composed of perovskite quantum dots synthesized from the designed material. The light-emitting layer is uniformly covered on the entire glass substrate using a spin coater at high speed (3000 rpm, 20 s), and then annealed for 10 min.
[0039] (2) Vacuum Evaporation: Vacuum evaporation is performed on the glass substrate that has undergone spin coating as described above. The treated glass substrate is placed in a vacuum evaporation chamber with a vacuum degree ≤2×10⁻⁶. -4 Pa, TPBi layer, LiF layer and Al electrode are sequentially deposited by thermal evaporation system. The specific evaporation of each layer is a conventional technique;
[0040] (3) Device packaging: The prepared organic electroluminescent device is sealed in a nitrogen atmosphere glove box with a water oxygen concentration of less than 1 ppm. Then, a glassy sealing cap with epoxy-type ultraviolet curing resin is used to cover the above film-forming substrate and UV curing is performed for sealing. The specific packaging is a conventional technique.
[0041] Comparative Example 1: CsCO3, OA, and ODE (20 mL) were added to a 50 mL three-necked flask. The mixture was dried under vacuum at 120 °C for 60 min, then nitrogen was introduced, and the solution was heated to 150 °C and held for 15 min to allow complete reaction of CsCO3 and OA. Finally, the solution temperature was lowered to 120 °C for further use. OA, OAm, PbBr2, and ODE (20 mL) were placed in a 50 mL three-necked flask and dried under vacuum at 120 °C for 60 min. Then, under a nitrogen atmosphere, OAm solution was injected into the mixture, and the reaction was allowed to proceed for 15 min, forming a clear and transparent solution. The temperature was then raised to 175 °C, and 2 mL of cesium oleate solution was rapidly injected into the flask. After reacting for 5–10 s, the reaction mixture was rapidly cooled in an ice-water bath to obtain a bright green CsPbBr3 quantum dot stock solution. The stock solution was divided into four centrifuge tubes and mixed with ethyl acetate at a volume ratio of 1:2. The mixture was centrifuged at 12000 rpm for 6 min, and the precipitate was dispersed in 3 ml of n-hexane. This purification process was repeated 2-3 times, and the final dispersion in n-hexane was then used for later use. Fabrication and performance evaluation of organic electroluminescent devices using ion-ligand-free perovskite quantum dots as the emitting layer:
[0042] The fabrication steps for organic electroluminescent devices using perovskite quantum dots synthesized without ion ligand doping as the emitting layer are as follows:
[0043] (1) Pretreatment of glass substrate: Select transparent electrode glass substrate (3.2×3.2mm) with indium tin oxide (ITO) film. Sonicate the glass substrate with indium tin oxide film with ITO cleaning solution, deionized water, acetone, isopropanol and ethanol for 30 minutes respectively. Then, put these substrates into an ultraviolet ozone cleaner for 15 minutes to obtain pretreated glass substrate.
[0044] (2) Spin coating: The pretreated glass substrate is spin-coated at low speed (500 rpm, 10 s) and high speed (3000 rpm, 120 s) using a spin coater to uniformly cover the entire glass substrate with PEDOT:PSS, and then annealed for 20 min. After cooling to room temperature, PVK is spin-coated on the PEDOT:PSS surface at high speed (3000 rpm, 120 s) for 60 s, and then annealed for 10 min. After cooling to room temperature, a light-emitting layer is spin-coated, which consists of perovskite quantum dots. The light-emitting layer is uniformly covered on the entire glass substrate using a spin coater at high speed (3000 rpm, 20 s), and then annealed for 10 min.
[0045] (2) Vacuum Evaporation: Vacuum evaporation is performed on the glass substrate that has undergone spin coating as described above. The treated glass substrate is placed in a vacuum evaporation chamber with a vacuum degree ≤2×10⁻⁶. -4 Pa, TPBi layer, LiF layer and Al electrode are sequentially deposited by thermal evaporation system. The specific evaporation of each layer is a conventional technique;
[0046] (3) Device packaging: The prepared organic electroluminescent device is sealed in a nitrogen atmosphere glove box with a water oxygen concentration of less than 1 ppm. Then, a glassy sealing cap with epoxy-type ultraviolet curing resin is used to cover the above film-forming substrate and UV curing is performed for sealing. The specific packaging is a conventional technique.
[0047] Evaluation of the photoelectric properties of perovskite quantum dots synthesized with DPCN-Br ligand doping and those without ligand doping.
[0048] Figure 1 This is a structural diagram of the device used in this invention.
[0049] Figure 2 The UV-Vis absorption and photoluminescence spectra of PQDs and DPCN-Br-PQDs are shown. The UV-Vis absorption peak of the perovskite film synthesized with DPCN-Br assistance is similar to that of the original perovskite film. Furthermore, no new sub-absorption peaks appeared after the introduction of DPCN-Br, indicating that the additive is located only at grain vacancies in the perovskite or passivates defects in the perovskite. Both films exhibit significant green luminescence at 511 nm, and the luminescence intensity is greatly enhanced after the addition of DPCN-Br to the perovskite.
[0050] Figure 3 Fourier transform infrared spectra of PQDs and DPCN-Br-PQDs are shown. Characteristic peaks of sulfone groups were observed in the infrared spectrum of DPCN-Br-PQDs, proving the presence of DPCN-Br on PQDs.
[0051] Figure 4 The JVL performance curves for PQDs and DPCN-Br-PQDs devices are given by... Figure 3 It can be seen that the introduction of DPCN-Br improves the brightness of the device and reduces the current density, thus obtaining a perovskite light-emitting diode with excellent performance.
[0052] The description of the above embodiments is intended to enable those skilled in the art to implement or apply the present invention. Suitable modifications to these embodiments will be apparent to those skilled in the art, and can be implemented in other embodiments without departing from the core concept or scope of the invention. Therefore, the scope of the invention is not limited to the embodiments shown herein, but should be determined based on the principles and unique features disclosed herein, attributing it to the broadest possible application.
Claims
1. A novel ionic thermally activated delayed fluorescence material, characterized in that, The thermally activated delayed fluorescence material has the structure shown in formula (1); Equation (1) 2. A method for preparing the ionic thermally activated delayed fluorescence material according to claim 1, characterized in that, The preparation method is as follows: Step 1: 6-(4-(((6-bromohexyl)oxy)methyl)phenoxy)-N,N-dimethylhexane-1-amine and 4-hydroxycarbazole are attached to the 4-position of carbazole by a substitution reaction to obtain intermediate 1, the structural formula of which is shown in formula (2). Equation (2) Step 2: 2,8-difluoro-dibenzothiophene, 5,5-dioxide and intermediate 1 are given by electrophilic substitution reaction to obtain intermediate 2, the structure of which is shown in formula (3); Equation (3) Step 3: Intermediate 2 and 1-bromoethane are subjected to a Menschutkin reaction to obtain the thermally activated delayed fluorescence ionic liquid DPCN-Br, the structural formula of which is shown in formula (1).
3. The preparation method of a deep blue photothermal crosslinked thermally activated delayed fluorescence material according to claim 2, characterized in that, The eluent for column chromatography in steps one and two is a mixed solution of petroleum ether, dichloromethane, and triethylamine, and the eluent for column chromatography in step three is petroleum ether and ethanol.
4. Application of an ionic thermally activated delayed fluorescence material in passivated perovskite quantum dots.
5. An electroluminescent device, characterized in that, The material as claimed in claim 4 is used as the light-emitting layer.
6. The electroluminescent device according to claim 5, characterized in that, The electroluminescent device is a QLED device.